Non-pulmonary Rhodococcus equi infections in patients with acquired immune deficiency syndrome (AIDS). Issue 5 (May 1987) - Fierer, J; Wolf, P; Seed, L; Gay, T; Noonan, K; Haghighi, P
Abstract : Rhodococcus equi, formerly known as Corynebacterium equi, was isolated repeatedly from the blood of two patients with the acquired immune deficiency syndrome (AIDS). Neither of the patients had pneumonia while they were bacteraemic, whereas pneumonia has been present in all previously reported cases of human infection with R equi. One of our patients had diarrhoea and the organism was isolated from a stool culture; the other patient had a large granulomatous soft tissue mass in his pelvis caused by R equi. Both isolates were resistant to penicillin and one produced a beta-lactamase. Both patients were treated with vancomycin but only one recovered.